Novel Micro- and Nanocellulose-Based Delivery Systems for Liposoluble Compounds - Casanova, Francisca; Pereira, Carla F.; Ribeiro, Alessandra B.; Freixo, Ricardo; Costa, Eduardo; E. Pintado, Manuela; Fernandes, João C.; Ramos, Óscar L. (Nanomaterials (Basel, Switzerland), 2021)
Poor aqueous solubility of bioactive compounds is becoming a pronounced challenge in the development of bioactive formulations. Numerous liposoluble compounds have very interesting biological activities, but their low water solubility, stability, and bioavailability restrict their applications. To overcome these limitations there is a need to use enabling delivering strategies, which often demand new carrier materials. Cellulose and its micro- and nanostructures are promising carriers with unique features. In this context, this review describes the fast-growing field of micro- and nanocellulose based delivery systems with a focus on the release of liposoluble bioactive compounds. The state of research on this field is reviewed in this article, which also covers the chemistry, preparation, properties, and applications of micro- and nanocellulose based delivery systems. Although there are promising perspectives for introducing these materials into various fields, aspects of safety and toxicity must be revealed and are discussed in this review. The impact of gastrointestinal conditions on the systems and on the bioavailability of the bioactive compounds are also addressed in this review. This article helps to unveil the whole panorama of micro- and nanocellulose as delivery systems for liposoluble compounds, showing that these represent a great promise in a wide range of applications.